2010
DOI: 10.1128/aem.02941-09
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Prey Chemical Warfare Determines the Expression of Biocontrol Genes by Rhizosphere-Associated Pseudomonas fluorescens

Abstract: Soil bacteria are heavily consumed by protozoan predators, and many bacteria have evolved defense strategies such as the production of toxic exometabolites. However, the production of toxins is energetically costly and therefore is likely to be adjusted according to the predation risk to balance the costs and benefits of predator defense. We investigated the response of the biocontrol bacterium Pseudomonas fluorescens CHA0 to a common predator, the free-living amoeba Acanthamoeba castellanii. We monitored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 48 publications
8
71
0
Order By: Relevance
“…Sclerosin, which exhibited almost no toxicity toward C. elegans, was unchanged with respect to gene expression in DF41 grown with the nematodes. These findings are similar to those reported by Jousset and coworkers, wherein cell-free supernatants of the amoeba Acanthamoeba castellanii were found to increase the expression of phlA (diacetylphloroglucinol [DAPG]), prnA (pyrrolnitrin), and hcnA in P. fluorescens CHA0 (22). Notably, there was a correlation between the level of expression and the toxicity of the encoded product, with the greatest increase in gene expression observed for DAPG, the most toxic metabolite tested (22).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Sclerosin, which exhibited almost no toxicity toward C. elegans, was unchanged with respect to gene expression in DF41 grown with the nematodes. These findings are similar to those reported by Jousset and coworkers, wherein cell-free supernatants of the amoeba Acanthamoeba castellanii were found to increase the expression of phlA (diacetylphloroglucinol [DAPG]), prnA (pyrrolnitrin), and hcnA in P. fluorescens CHA0 (22). Notably, there was a correlation between the level of expression and the toxicity of the encoded product, with the greatest increase in gene expression observed for DAPG, the most toxic metabolite tested (22).…”
Section: Discussionsupporting
confidence: 79%
“…We discovered that DF41 is capable of killing C. elegans through two distinct modes; the first involves exposure to toxic metabolites, while the second entails biofilm formation on the nematode surface. It has been reported that bacteria are capable of responding to predator cues through altered expression of toxin-encoding genes (7,22,23). To see if the same holds true for DF41, we cocultured bacteria with C. elegans and monitored the expression of genes associated with exometabolite production.…”
mentioning
confidence: 99%
“…In one recent study on predator-prey chemical warfare involving P. fluorescens as the prey and another amoeba (Acanthamoeba castellanii) as the predator, pyrrolnitrin was toxic, and supernatants of amoeba cultures strongly induced the production of the molecule (25). Farmer resistance and nonfarmer sensitivity would indicate that the farmers adapted to harboring a potentially lethal symbiont.…”
Section: Differential Effect Of Pyrrolnitrin On Farmer and Nonfarmermentioning
confidence: 99%
“…A type VI secretion system confers cytotoxicity of Vibrio cholera to D. discoideum (23) through the translocation of an actin cross-linking protein (24). The soil bacterium Pseudomonas fluorescens induces the expression of genes involved in the production of certain extracellular toxins in response to chemical cues from A. castellani (25).…”
mentioning
confidence: 99%